Entrepreneurial intentions at Further Education and Training colleges in South Africa - Skosana, B Vusi; Urban, Boris (South African Journal of Higher Education, 2018)
The relevance of entrepreneurship is underscored in the public policy domain where a wide range of government policies support the development of entrepreneurship, with Further Education and Training (FET) colleges seen as critical role-players. Research shows that entrepreneurship education increases a student’s self-confidence and overall attitudes, which in turn increases their perceptions of feasibility and desirability of pursuing entrepreneurship as a career. Recognising the challenge for FETs is to ensure that graduates are also equipped for self-employment, this study investigates entrepreneurial intentions of final year FET college students in four provinces. Statistical analysis reveals high levels of intentions amongst differing groups irrespective of personal (gender) or contextual attributes (in rural, vs. metro-township, vs. urban FET colleges). Implications can be advanced to the policy domain where it needs to be stressed that government initiatives will affect entrepreneurship development only if these policies are perceived in a way that influences intentions, in particular an individual’s conviction, as characterised by general attitudes towards entrepreneurship.